Transit camp for construction workers, Pataudi, Haryana - Ratan, Rupeander (SPA, BHOPAL, 2018)
The Construction industry is the second largest economic generator in India, but unfortunately no law or standard regularises the condition of living of the construction workers on sites. As architects, the design has a greater role in solving their issues and in helping they bring about a shift their lifestyles. The attempt of this thesis is to arrive at a sustainable model along the lines of the social art of architecture. The design program encompasses resolution of a prototype which can be replicated across the nation, as a patented model following a well-devised policy framework. The prototype unit is a ground storied system of housing modules, which can be used in places where the construction site area is large enough to provide for workers accommodation. The materials to be considered for the shelters are climate responsive and can be RESOLD or REUSED as per the requirements of the builder. The limitation of this thesis is the duration of the construction projects that may consider the worker's shelters need to be at least 3 years to have optimal financial security for enabling the use of the above-said models. My thesis project looks at demonstrating this idea by proposing a Transit amp for construction workers in Pataudi, Haryana.
Keywords: BARC2013; Transit camp-construction workers-Pataudi, Haryana; Design; Construction workers on sites